2005
DOI: 10.1079/ber2005366
|View full text |Cite
|
Sign up to set email alerts
|

Restriction fragment length polymorphisms of different DNA regions as genetic markers in the hoverfly Episyrphus balteatus (Diptera: Syrphidae)

Abstract: A polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis using mitochondrial (A+T-rich region; mtDNA) and genomic (zen-region; nDNA) DNA was performed on 182 female individuals of Episyrphus balteatus (DeGeer), a widespread aphidophagous hoverfly with supposed migratory behaviour. Specimens originated from 13 sampling sites in six European countries. The analyses revealed 12 and 18 haplotypes, respectively, for the two DNA types, several of them with a wide distribution, althoug… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 44 publications
1
20
0
Order By: Relevance
“…Similarly, another common migratory hoverfly Episyrphus balteatus (De Geer 1776) revealed that European populations are connected to a large extent and form one large panmictic population (Hondelmann et al. ). However, molecular study of another widely distributed hoverfly species Cheilosia vernalis (Fallen 1817) indicated that historic factors may play a significant role in genetic divergence among geographically distant populations (Milankov et al.…”
Section: Discussionmentioning
confidence: 99%
“…Similarly, another common migratory hoverfly Episyrphus balteatus (De Geer 1776) revealed that European populations are connected to a large extent and form one large panmictic population (Hondelmann et al. ). However, molecular study of another widely distributed hoverfly species Cheilosia vernalis (Fallen 1817) indicated that historic factors may play a significant role in genetic divergence among geographically distant populations (Milankov et al.…”
Section: Discussionmentioning
confidence: 99%
“…Its color patterns may appear wasp-like to animals, such as birds, protecting it from predation24. Often exhibiting dense migratory swarm behavior, this, and the resemblance to wasps, may panic unaware people25. Its feeding habit is rare among adult flies, as it is capable of crushing pollen grains as a food source26.…”
mentioning
confidence: 99%
“…Finally, morphological differences are also often associated with genetic structure (Villemant et al 2007, Francoy et al 2011, Vicente et al 2011, Neto et al 2013. However, previous studies found no evidence for genetic structure either in relation with geographical origin (Hondelmann et al 2005, Raymond et al 2013b, or with overwintering strategy (Raymond et al 2013a) in E. balteatus. This lack of genetic structure may reduce the degree of morphological variation between individuals originating from different regions or using different overwintering strategies.…”
Section: Wing Morphology As a Tool For The Characterization Of Migratmentioning
confidence: 78%
“…Although most aphidophagous hoverfly species are migratory and provide ecosystem services that are important for agriculture, issues related to migration have rarely been addressed in these species. Lack of genetic differentiation between E. balteatus overwintering strategies (Raymond et al 2013a) as between geographical origins (Hondelmann et al 2005, Raymond et al 2013b leads to consider alternative approaches to understand migration patterns of this species.…”
Section: Introductionmentioning
confidence: 99%